Problem-Based Learning melalui Belajar Kooperatif Think-Pair-Share untuk Meningkatkan Pemahaman Konsep Mahasiswa Calon Guru - Ahmad Muzaki; Purwanto Purwanto; Muchtar Abdul Karim (IKIP Mataram, 2015)
This study aims to describe the PBL process through cooperative TPS learning so that it can improve the understanding of fourth-semester students of the IKIP Mataram Mathematics Education Department on integer division. This study was a classroom action research (CAR) which was applied to 44 fourth semester students of the mathematics education study program IKIP Mataram. The instruments of data collection included lecturer and student activity sheets, tests, interview guidelines, field notes, and documentation. The criteria of success in this study are based on (1) data on observations of student activities. (2) observational data on lecturer activity, and (3) test results data. The results of the first cycle showed that (1) the observational data of student activities were in the fairly active category, (2) the results of lecturer activity observation data were in a fairly good category, and (3) the average score of student test results was less than 68. The results of the research in the second cycle showed that (1) the observational data of student activities were in the active category, (2) the observation data of lecturers' activities were in the good category, and (3) the average score of student test results was more than or equal to 68 Cycle II, all the success criteria have been achieved, so that the application of PBL through TPS cooperative learning can improve the understanding of integer division material in fourth semester students G mathematics education study program IKIP Mataram academic year 2011/2012.